Residents’ perception of community based sport tourism related activities in Sarawak - Abdullah, Mohd. Shafiq (2015)
This study investigates host community perceptions and expectations towards the impact of community based sport tourism related activities in Kapit-Baleh, Sarawak and how it affects the host residents’ daily livelihood in the tourism destinations. The sample populations consisting of longhouse residents, participants, tour operators and local council officer who are directly involved in the activities. This study integrates social exchange theory and as the framework for investigating the individual and societal components of perceptions of sport tourism in residents’ attitudes. Community based sport tourism event impact assessment (COMSTEIA) was established as a guidelines process for this study to assess the level of expectation and perception of the local host community. The research was conducted by using qualitative and quantitative perspectives. Throughout the study, data is collected by using different methods which reflects that triangulation was largely utilized in the research. Three hundred and eighty respondents completed the survey Factor analysis is use to identify the underlying dimension and variables. Accordingly, the study proposes three research questions: (1) level of perception (2) level of perceived expectation and (3) importance of the activities. The findings of this study indicate that the range of level of expectation and perception varied from different dimension. There seem to be enough related evident at this point to conclude there is an association between support for tourism to cultural and economic development and perceptions of its positive impacts on the local community. These findings are consistent with the social exchange theory to those who view these activities as a catalyst for development. The host community have positive perception towards economic benefits before the activities but at the end of the activities the host community give negative perceptions based on the benefit from the activities as further explained in the Social Exchange Theory. It has been established that host community from different longhouse might perceive the activities as unacceptable, while in other longhouse, the activities maybe more acceptable. Further research opportunities are presented by these conclusions and may be further explored. There is a need to formulate strategies, processes and frameworks to engage and empower host community involve in community based sport tourism related activities. The result of this study provides a platform for local authority to reflect upon and revise their modes of governance for community based sport tourism related activities.